The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1016/j.jceh.2021.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex PCR-based Sequencing of ATP7B Gene in Wilson's Disease – A Preliminary Study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The correlation between genotype and phenotype for these variants is controversial. While some papers document severe neurological impairment and K–F rings in patients during the first or early second decade of life, others report hepatic presentations [ [24] , [25] , [26] , [27] , [28] ]. It is worth mentioning that most studies have reported a lack of correlation between ATP7B gene variants and the phenotype.…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%
“…The correlation between genotype and phenotype for these variants is controversial. While some papers document severe neurological impairment and K–F rings in patients during the first or early second decade of life, others report hepatic presentations [ [24] , [25] , [26] , [27] , [28] ]. It is worth mentioning that most studies have reported a lack of correlation between ATP7B gene variants and the phenotype.…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%